Comparison of Combination of Sclerotherapy and Tiersch's Procedure with Perineal Rectopexy with Mesh in Children - Reza Ebrahimi; Baharah Ahmadi; Mehrdad Hosseinpour (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Perineal rectopexy is a method for surgical treatment of rectal prolapse in children, but its accomplished using different techniques. We investigated the combination therapy of Tiersch's operation and sclerotherapy and compared its outcome with mesh rectopexy with talc. Materials and Methods: A total of 80 children with rectal prolapse were selected and divided in two groups. In the control group rectopexy was performed by perineal mesh rectopexy with talc. In the case group, injection of 30% saline and, Tiersch's operation were performed. The parameters used to compare the success of interventions were improvement of incontinence and constipation and a low rate of recurrence. Result: Our results showed that the rate of improvement in constipation and incontinency was not significantly different in the two groups. The recurrence rate was 1.6 % in both groups in one year of follow up. Fifteen patients (37.5%) in the control group had severe anxiety and pain during the extraction of mesh. The length of hospitalization was 6.2± 0.94 in the controls and 0.86± 0.63 days in case group. Conclusion: Our study suggests the combination perineal therapy (T+S) as an alternative approach for children who have limitations regarding talc rectopexy or the high hospital charges related to this approach.